Progress on the Development of Techniques to Remove Contaminants from Wastewater: A Review - Yadav, Saurabh; Kamsonlian, Suantak (Applied Science and Engineering Progress, 2023)
The continuous depletion of fresh drinking water resources throughout the world has increased the necessity for the development of new techniques for wastewater treatment and recycling process. Domestic, industrial and agricultural wastes are major sources of aquatic contamination all over the world. Before discharging wastewater into natural water bodies, it must be treated. Apart from primary, secondary and tertiary treatment, membrane separation techniques and electrochemical membrane bioreactors for wastewater treatment have all been studied in this review paper. The electrochemical membrane bioreactor (EMBR) system has a lot of potential for treatment of wastewater and energy recovery. These novel EMBR techniques give feasible solutions for renewable treatment of wastewater and resource resumption.